Revalidation of Mazama rufa (Illiger 1815) (Artiodactyla: Cervidae) as a Distinct Species out of the Complex Mazama americana (Erxleben 1777) - Peres, Pedro H. F.; Luduvério, Douglas J.; Bernegossi, Agda Maria; Galindo, David J.; Nascimento, Guilherme B.; Oliveira, Márcio L.; Sandoval, Eluzai Dinai Pinto; Vozdova, Miluse; Kubickova, Svatava; Cernohorska, Halina; Duarte, José Maurício Barbanti (Frontiers in Genetics, 2021)
The red brocket deer Mazama americana (Erxleben, 1777) is considered a polyphyletic complex of cryptic species with wide chromosomal divergence. Evidence indicates that the observed chromosomal divergences result in reproductive isolation. The description of a neotype for M. americana allowed its genetic characterization and represented a comparative basis to resolve the taxonomic uncertainties of the group. Thus, we designated a neotype for the synonym Mazama rufa (Illiger, 1815) and tested its recognition as a distinct species from the M. americana complex with the analysis of morphological, cytogenetic and molecular data. We also evaluated its distribution by sampling fecal DNA in the wild. Morphological data from craniometry and body biometry indicated an overlap of quantitative measurements between M. rufa and the entire M. americana complex. The phylogenetic hypothesis obtained through mtDNA confirmed the reciprocal monophyly relationship between M. americana and M. rufa, and both were identified as distinct molecular operational taxonomic units by the GMYC species delimitation analysis. Finally, classic cytogenetic data and FISH for whole chromosome painting showed M. rufa with a karyotype of 2n = 52, FN = 56. Fifteen rearrangements separate M. rufa and M. americana (sensu stricto) karyotypes, which confirmed their substantial chromosomal divergence. This divergence should represent an important reproductive barrier and allow its characterization as a distinct and valid species. Genetic analysis of fecal samples demonstrated a wide distribution of M. rufa in the South American continent through the Atlantic Forest, Cerrado and south region of Amazon. Thus, we conclude for the revalidation of M. rufa as a distinct species under the concept of biological isolation, with its karyotype as the main diagnostic character. The present work serves as a basis for the taxonomic review of the M. americana complex, which should be mainly based on cytogenetic characterization and directed towards a better sampling of the Amazon region, the evaluation of available names in the species synonymy and a multi-locus phylogenetic analysis.